A CORRELATIONAL STUDY BETWEEN STUDENT’S ENGLISH INTEREST, VOCABULARY MASTERY, AND STUDENT’S ACHIEVEMENT - Sulaiman, Sulaiman (IKIP PGRI Pontianak, 2019)
The study is aimed to reveal the correlation between student’s English interest, vocabulary mastery toward student’s English achievement of the second-semester Students of Islamic Education Department of Teacher Training and Education Faculty of IAIN Pontianak in the academic year of 2017/2018. This study used a test, a questionnaire, and documentation to collect the data. The population of the study is all of the second-semester students while the sample is 50 students taken by cluster random sampling technique. The techniques used to analyze the data are simple and multiple correlation and regression by using SPSS 23. The results of the study show that there is a positive correlation between student’s English interest, and vocabulary mastery toward student’s English achievement. The positive correlation indicates that English interest, and vocabulary mastery line together with student’s English achievement.keywords: correlation, english interest, vocabulary mastery english achievement